The effectiveness of distance education in the kindergarten stage in the city of Taif from the point of view of teachers - Al-Harthy, Amal Saad (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effectiveness of distance education in the kindergarten stage in Taif from the teachers’ point of view, and to achieve the goal, the study followed the descriptive approach, which was based on the application of a questionnaire that measures the opinions of kindergarten teachers towards distance education, and the difficulties of using distance education for the kindergarten stage From the teachers ’point of view, and after making sure of its validity and stability, it was applied to a random sample of (308) teachers. The study’s questions were answered through the use of appropriate statistical methods to arrive at the results of the study, the most important of which are the following: The study revealed the views of kindergarten teachers in Taif. About distance education, with a mean of (2.90), which indicates the average approval of the sample members. The study sample agreed on the difficulties of using distance education in the kindergarten stage with a large degree of agreement, with an arithmetic average of (3.67). The study showed that there were no statistically significant differences between kindergarten teachers’ opinions towards distance education due to a variable (years of experience). The study showed that there were no statistically significant differences between kindergarten teachers ’viewpoints regarding distance education difficulties due to variable (years of experience).